Analisis Hambatan Samping terhadap Kinerja Lalu Lintas Menggunakan Regresi Linier Berganda - Eriza Auliansyah; Felly Misdalena; Panti Wahyuningsih (Jurnal Konstruksi, 2025)
The purpose of this study is to examine how side obstacles affect traffic flow on Jalan Ikan Sebelah in Bandar Lampung City. Roadside parking, stopped cars, cars entering and exiting, pedestrians, and slow-moving vehicles such as bicycles and pedicabs are all considered side obstacles. To assess the contribution of each side obstacle, this study uses multiple linear regression and traffic performance analysis based on the 2014 Indonesian Road Capacity Guidelines (PKJI). With light vehicles traveling at only 19.18 km/h during rush hour, the results show that the degree of saturation reached a value of 0.80, indicating a category D road service level. Vehicle parking, stopping, and entering and exiting had the greatest side obstacles, with an obstacle value of 548.8 smp/hour. These findings confirm that managing side constraints is crucial for improving the capacity and performance of road sections in areas with high social and economic activity.